Starburst amacrine cells form gap junctions in the early postnatal stage of the mouse retina - Maruyama, Takuma; Ishii, Toshiyuki; Kaneda, Makoto (Frontiers in Cellular Neuroscience, 2023)
Although gap junctional coupling in the developing retina is important for the maturation of neuronal networks, its role in the development of individual neurons remains unclear. Therefore, we herein investigated whether gap junctional coupling by starburst amacrine cells (SACs), a key neuron for the formation of direction selectivity, occurs during the developmental stage in the mouse retina. Neurobiotin-injected SACs coupled with many neighboring cells before eye-opening. The majority of tracer-coupled cells were retinal ganglion cells, and tracer coupling was not detected between SACs. The number of tracer-coupled cells significantly decreased after eye-opening and mostly disappeared by postnatal day 28 (P28). Membrane capacitance (Cm), an indicator of the formation of electrical coupling with gap junctions, was larger in SACs before than after eye-opening. The application of meclofenamic acid, a gap junction blocker, reduced the Cm of SACs. Gap junctional coupling by SACs was regulated by dopamine D1 receptors before eye-opening. In contrast, the reduction in gap junctional coupling after eye-opening was not affected by visual experience. At the mRNA level, 4 subtypes of connexins (23, 36, 43, and 45) were detected in SACs before eye-opening. Connexin 43 expression levels significantly decreased after eye-opening. These results indicate that gap junctional coupling by SACs occurs during the developmental period and suggest that the elimination of gap junctions proceeds with the innate system.